Conservation, Phytoremediation Potential and Invasiveness Status of Bali Botanic Garden Aquatic Plant Collection - Farid Kuswantoro (Journal of Tropical Biodiversity and Biotechnology, 2020)
Bali Botanic Garden (BBG) aspires to conduct conservation and research of eastern Indonesian plant species, including the aquatic plant species. These were important as aquatic plant species could be ecologically threatened, beneficial or even dangerous. As scientific data of BBG aquatic plant species collection was limited, we proposed this study to provide researchers and garden managers with data to conduct research, collection and maintenance of the garden aquatic plant collection. The study was carried out by sourcing list of BBG collected plant species data for its aquatic plant species. Literatures study was then carried out to gain information regarding the plant species’ heavy metal phytoremediation, conservation and invasiveness status while data analysis was conducted descriptively. The study result showed that 38 collection numbers of aquatic plant species collected in BGG were placed in five sites within the garden with 94% of all the aquatic plants collection came from Lesser Sunda Islands. Eleven aquatic plants species were listed as Least Concern by IUCN Red List. Fourteen species of collected aquatic plants were proved to possessed phytoremediation potential toward numerous heavy metal pollutants, while six species were listed as an invasive alien plant species in Indonesia. All of the provided data should be enabled the botanic garden stakeholders to come up with ideas in the research and maintenance effort of BBG aquatic plant collection.